Individualism, Polarization and Recovery from the COVID-19 Crisis - Barry Eichengreen (Intereconomics, 2020)
Political polarization, meaning sharp differences in the political ideologies and preferences of the partisans of different parties, implies that members of one party are more likely to dismiss the policies and recommendations of spokesmen and appointees of the other party on the grounds that those policies and recommendations are informed by value systems inimical to their own. In the US, this means that when spokesmen for one party endorse masks, members of the other party reject them instinctively and automatically.
Keywords: 330; Coronavirus; Epidemie; Individualismus; Kommunitarismus